Survei Keterampilan Dasar Bermain Futsal Pada Peserta Didik SMA Negeri 1 Kota Tual - Nuhuyanan, Muhamad Rizki; Anaktototy, J.; Divinubun, S. (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research is a descriptive statistical research that aims to provide a picture of the reality of the basic technical skills of futsal players in extracurricular futsal at SMA Negeri 1 Tual. This research was conducted at SMA Negeri 1 Tual, which is located in Pulau Dullah Selatan District, Tual City. Data collection techniques use test methods by students with two trials. The results of this study show that the basic skills of playing futsal in students of SMA Negeri 1 Tual in 2024 are categorized as very good 5 students (20%), good 10 students (40%), sufficient 4 students (16%), less than 5 students (20%) and less than once 1 student (4%). This means that the level of basic skills in futsal games possessed by extracurricular futsal students at SMA Negeri 1 Tual in 2024 is classified as good. However, for those who are still in the Sufficient, Less and Less categories, they need to be paid more attention to and improve their techniques and basic skills in playing futsal for extracurricular futsal students at SMA Negeri 1 Tual